Hammerhead highway - Houston, Rodd.; Lucas, Thomas; National Geographic Television & Film. ([England?] : National Geographic : FremantleMedia Enterprises, 2010)
Sharks have thrived in the oceans for over 350 million years, but around 20 million years ago a new species emerged in the fossil records in a form unlike ever seen before ... the Hammerhead shark. Why did this bizarre looking creature evolve and how has it survived? Hidden beneath the surface of the sea is a phenomenon we know almost nothing about. On land, scientists have long studied the great animal migrations, but in the ocean some of the most spectacular events go almost unnoticed. Now, with an international team of scientists, National Geographic examines the movements of hammerhead sharks. How do they navigate? Do they possess an internal compass? What prompts them to seek out distant destinations? In a world threatened by overfishing and declining marine populations, understanding their behavior may be the key to ensuring hammerhead survival.
Narrator, Rodd Houston.
Keywords: Documentary television programs; Hammerhead sharks; Nonfiction television programs; Wildlife television programs